La Revolución ilustrada: la guerra civil mexicana en la literatura juvenil - Marion Gautreau (Caravelle)
In this article we shall study the scarce books for the youth published in Mexico about the theme of the Revolution, in order to show how their authors have apprehended their own history and iconography to be able to restore it to 21st century children. Between a pedagogical approach, as well as an artistic and entertaining one, these cultural objects offer a contemporary representation of the Revolution which reveals the gap between Mexicans living today and this emblematic war belonging to their history.